Characteristics of Dispersed Latin Squares - Mahfooz, S. Z.; Khan, Y. (The Nucleus, 2020)
Experimental designs widely use Latin squares for controlled testing to understand causal processes. Among many existing Latin squares for a given order, a design of experiment may need a specific Latin square that offers its treatments (symbols) scattered at the desired locations. There is a need to study systematic dispersion of symbols in Latin squares to assist effective research designs. This paper describes the attributes and applications of one of such designs known as Latin square of diamond dispersed pattern